A COMPLIANCE–QUALITY ASSESSMENT OF ESG DISCLOSURE: EVIDENCE FROM BANK BRI UNDER SEOJK 16/2021 FRAMEWORK - Satya Awang Kurniawan; Eko Ganis Sukoharsono (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes. This study analyzes Bank BRI’s ESG disclosure in terms of compliance with sustainability report presentation and ESG disclosure quality in its sustainability report for the period 2021 – 2023, based on SEOJK 16/2021. Research Methods This study employs a qualitative approach and content analysis. Research Results and Findings. The results show that Bank BRI has presented its sustainability report for the period 2021 – 2023 in accordance with SEOJK 16/2021, with consecutive scores of 80.13, 88.00, and 87.25 on a scale of 100. The ESG disclosure analysis identifies several areas that require special attention. The implications of this research are expected to be the basis for further research to measure and analyze corporate sustainability reports in Indonesia.